Pengaruh Padat Tebar Yang Berbeda Terhadap Laju Pertumbuhan dan Tingkat Kelangsungan Hidup Benih Ikan Lele Dumbo (Clarias Gariepinus) Budidaya Ikan Dalam Ember Budikdamber - Yayuk Tri Pamungkas; Titin Liana Febriyanti; Endang Sri Utami (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
The aquaculture sector is one source of food production whose development in Indonesia reached 6,979,750 tonnes or 95.80%. Therefore, it can contribute to the community's nutritional adequacy rate. Fisheries cultivation must be encouraged, because it plays an important role in improving the community's economy. Catfish production in Indonesia reached 1.06 million tons and 19,550 tons in Lampung. Catfish can be cultivated with various types of pools including tarpaulin, concrete, soil, biofloc and bucket pools. The aim of cultivating in buckets is as a form of updating appropriate technology through cultivating in buckets and creating nutritional gardens. The levels of ammonia, nitrite and nitrate in catfish ponds with plants will be lower than in conventional ponds without aquaponics. The experiment was conducted with a Completely Randomized Design (CRD) with four treatments and three replications (P1=1 head/liter, P2=2 head/liter, P3=3 head/liter and P4=4 head/liter). The best absolute weight growth rate was 3.1 grams, absolute length growth rate was 9.1 cm, and survival rate was 81%, accompanied by other water quality parameters such as temperature (26.5 - 28.4oC), pH (6.5- 6.8), DO (3-4 mg/L), TDS (135- 145 ppm).